Intelligent prostatic cancer seed implantation device - JIANG JINGANG; XUE LE; ZHANG YONGDE (2017)
The invention relates to the field of medical prostatic-cancer robots, in particular to an intelligent prostatic cancer seed implantation device. The device is small in size, compact in structure and convenient to use, and a guiding template is omitted. Three-dimensional space motion of an implantation needle is achieved through a three-dimensional driving platform, so that the structure and motion of the intelligent prostatic cancer seed implantation device are more stable by using a frame structure and an auxiliary supporting motion platform, outage falling is prevented by using a vertical falling-prevention device, and meanwhile a sliding rod is tightly held by using a vertical-directional electromagnetic holding device during motion stopping to make the needle feeding motion of the device more stable. 本发明涉及前列腺医疗机器人领域，具体涉及种智能前列腺粒子植入装置。该装置体积小、结构紧凑、使用方便、省去了导向模板；通过三维驱动平台实现植入针的三维空间运动，使用框架结构和辅助支撑运动平台使其结构和运动更稳定，使用垂直防坠落装置防止断电坠落，同时使用垂直方向电磁抱紧装置，在运动停止时抱紧滑杆使其在进针运动时更稳定。